Perbedaan Kompetensi Antar Guru PAI Terasertifikasi Dengan Belum Tersertifikasi Pada MTs Di Kabupaten Pontianak - Sofanudin, Aji (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
This study aims to know (1) are there differences in teacher competence PAI MTs between the certified and that has not been certified (2) Are there differences in teacher competence PAI MTs sassociated with working period (3) Are there differences in student learning outcomes PAI MTs are educated by teachers who are certifid and not certified teachers, (4) Are there differences in student learning outcomes PAI MTs in terms of working lives of teachers, and (5) How is teacher competency profile PAI MTs which include pedagogical competence, personality, professional, and sosial. This research approach is quantative using causal comparative merhod. As a result, (1) There is a difference between teacher competence PAI-certified MTs and that has not been certified in the district of pontianak, (2) There is a difference in PAI MTs teacher competence in terms of teachers’ working lives (3) There is a difference in student learning outcomes PAI MTs are trained by certified teachers and teachers who have not certified, (4) There is a difference in learning outcomes of participants trained MTs PAI related to teachers’ working lives (5) Profile PAI MTs teacher compotence which include pedagogical competence, personalty, professional, and sosial in the district of pontianak as a whole meet the good category